Interpreting German : - Boser, Ursula (Routledge, 2001)
This innovative language course uses liaison interpreting to teach spoken German to advanced students. Designed to provide an alternative to conversation classes, it is a highly effective aid to language acquisition and consolidation. Interpreting German will improve students' confidence in speaking and discussing a wide variety of contemporary topics